The Future Burden of Public Pension Benefits A Microsimulation Study - Leif Andreassen; Dennis Fredriksen; Olav Ljones (Statistics Norway, Research Department, 1994)
The microsimulation model MOSART is used to analyse the long run development in disability and old-age pensions covered by the Norwegian National Insurance System. The number of pensioners will increase relative to the number of workers, leading to a growing tax burden on future generations. It is found that among those born before the year 2000, early generations possess a larger pension wealth (the discounted value of payments and received benefits) as a per cent of life time labour income than later generations. The paper discusses changes in the rules for determining pension benefits and the consequences of going from a pay-as-you-go system to a funded system.
Keywords: H5; J1; 330; Disability; demography; microsimulation; pension benefits.